공감각 이론에 의한 시후각 융합에 관한 연상 메커니즘 연구 - 향수 용기를 중심으로 - 주예요(Zhu, Rui Yao); 민자경(Min, Ja Kyoung) (기초조형학연구, 2024)
오늘날 향수 시장은 지속적인 성장을 하고 있으며 제품 간의 경쟁도 점점 더 치열해지고 있다. 이와함께 물질적 생활 수준이 계속 높아짐에 따라, 소비자들이 향수를 구매하는 이유는 더 이상 상황에 따른 필요 때문이 아니라, 자신의 감각적 경험과 자기만족을 충족시키기 위한 것으로 변화했다. 따라서소비자들의 물질적 요구를 충족시키는 동시에 정서적 요구에도 주의를 기울여야 한다. 본 연구의 목적은 향 타입의 특성과 의미론적 선호도를 이해하는 것으로, 즉 향 타입과 감성 평가 단어의 상관관계를탐구하고 성별에 대해 향수 용기의 차이 연구를 한다. 디자이너가 소비자의 감각적 경험에 일치하는향수 용기를 디자인하기 위한 기본 데이터 및 디자인 전략을 제공하는 것이다. 본 연구에서는 먼저 문헌조사 방법과 사례 분석 방법으로 향수 용기 디자인의 주요 요소(색상, 형태, 재질)를 정리하여 다음에 문헌조사로 의미 형용사를 선정하고 마지막으로 설문조사를 통해 시후각 융합의 공감각 실험을 실행했다. 실험 데이터는 SPSS로 신뢰성 분석, 평균치 분석, 상관관계 분석, 주성분 분석 및 독립표본 T검정 분석 등 데이터 처리하여 실험 데이터의 신뢰성, 향 타입과 향수 용기 시각적 요소 간의 의미론적 선호도 차이 및 상관 관계, 향의 시각 특성, 성별 차이로 인한 영향에 대해 논의했다. 분석 결과를정리하면 다음과 같다. (1) 향기와 시각 및 후각 요소 사이에 유의한 연관성이 있다. (2) 향수 조성의차이에 기초하여 시각적 의미 평가어에 대한 피험자의 판단 및 연결에 유의한 차이가 있다. (3) 향과시각적 요소에 대한 남성과 여성의 성별 연상적 차이는 주로 색상에 반영되고 재질은 차이가 있지만영향이 적었으며 형태에는 차이가 거의 없는 것으로 나타났다. 이 연구는 향수 소비자의 감각 경험에부합하는 향수 용기 디자인을 공식화하기 위한 이론적 근거와 특정 전략을 제공하길 희망한다. Nowadays, the fragrance market continues to grow, and the competition between products isbecoming increasingly intense. Meanwhile, as material living standards continue to rise,consumers are buying perfume not out of necessity, but to satisfy their sensory experiences andpersonal satisfaction. So While meeting the material needs of consumers, attention should also bepaid to emotional needs. The aim of this study is to understand the characteristics and semanticpreferences of different fragrance types, specifically by exploring the correlation betweenfragrance types and emotional evaluation words, and to investigate gender differences in perfumecontainer. This provides fundamental data and design strategies for designers to create perfumecontainer that aligns with consumers’ sensory experiences. In this study, the main factors(color,shape, and material) of perfume container design were summarized by literature study and caseanalysis method. Then, semantic adjectives were selected by literature study. Finally, asynesthesia experiment of visual and olfactory sense was conducted through a questionnaire. Theexperimental data were processed by SPSS for reliability analysis, Mean value analysis,correlation analysis, principal component analysis, and independent samples T-test. Thereliability of experimental data, semantic preference differences and correlation between aromatypes and visual elements of perfume containers, aroma types visual characteristics, the effectsof gender differences were discussed. The analysis results are summarized as follows: (1) Thereis a significant correlation between fragrance and visual as well as olfactory factors. (2) Basedon differences in fragrance composition, there are significant differences in participants’judgments and associations with visual meaning evaluation words. (3) Gender differences infragrance and visual elements are primarily reflected in color, with material showing somedifferences but less impact, and shape showing minimal differences. This study hopes to providetheoretical foundations and specific strategies for designing perfume container that aligns withconsumers’ sensory experiences. KCI Citation Count: 0